Predictors of functional state degradation in adults with congenital heart disease at late follow up period - Lebid, I. H. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Adults with congenital heart disease (CHD) have good follow-up in the early postoperative period, but late postoperative period require further examination. The purpose of the work was to reveal predictors of a functional condition deterioration in adults with the CHD (after pulmonary autograft operation, PAO) by an estimation the quality of a life (QL) and physical working capacity (PWC). Material and methods. From 01 Jan. to 31 Dec 2016 there were examined 46 consecutive adults elder 18 years. Gr.A (n=22) patients after PAO (Gr.A1 n=8 with NYHA I, Gr.A2 n=14 with NYHA II-III), Gr.B (n=24) healthy adults. Results. In Gr.A mean age 21.6±0.8 years (from 18 to 30 years), male (n=14; 63.6%), Gr.B– 22.7±1.3 years (from 18 to 28 years), male (n=14; 58.3%). Test 6MWT (Gr.A 429.6±22.2m, Gr.B 593.3±7.6m, p<0.01; Gr.A1 533.8±26.7m, Gr.A2 377.1±20.6m. p<0.01). Second stage Systolic BP (Gr.A1 153.8±6.0; Gr.A2 150.4±5.8mmHg) Gr.B (139.8±3.3 p <0,05). PWC 170 in Gr.A2 (745.7±72. 2 kgm/min), Gr.A1 (1035.0±82.6 kgm/min p<0,05) and Gr.B (1041.4±82.5 kgm/min p<0.05, p <0.01). Vo2 in Gr.A2 (2.5±0.1 l/min), Gr.B (3.0±0.1 l/min, p<0.05). In Gr.A2 gradients on PA conduit were (37.8±6.1), Gr.A1 (27.3±4.8 p<0.05) and in Gr.B (8.1±3.1 p<0.01). Indexes of QoL were in Gr.A2 PF (78.6±5.0), BP (66.0±6.9), GH (59.8±5.7) and SF (70.5±6.5), in Gr.A1 PF (83.1±4.0) were worse compare with Gr.B (94.2±1.6; 81.3±4.8; 75.0±4.4; 85.4±3.4, respectively, p<0,05). Conclusions. All patients after surgical correction of CHD are necessary to study exercise performance using the pro-posed method and estimate QL in late postoperative period.